Improvised and Self-taught Bookkeeping: Evidence from a WWII Captive’s Diary - Diakomihalis, Mihail (International Conference on Business and Economics - Hellenic Open University, 2023)
This paper aims to contribute to the existing literature on the issue of the accounting utility not for business reasons but for non-accountants and from the point of view of everyday life financial needs and human survival. In addition, this paper aims to reveal conclusions from the application of accounting by an ordinary essentially illiterate person, including that self-taught accounting is connected to the principles of accounting and modern application experience. Applying a qualitative-determinative analysis of a handwritten bookkeeping Diary, revealed that several accepted accounting principles were applied, even instinctively, by the illiterate young person. The improvised bookkeeping suggests that basic accounting knowledge derives from the specific needs of the individual and is configured according to specific circumstances of time and place and to the ease of understanding basic accounting theory and skills. The choice to use accounting, and the sanctuary and therapeutic value of accounting as bulwark in the worst possible circumstances reveals another option of social dimension of accounting. The accounting application as a means of finding structure and guidance in an unknown world and within a tragic environment helped extremely to turn the young refugee’s disaster to a success story. The few pages from the hand-written diary of an ex WWII captive is the quite unique and interesting material this paper is constructed on and consist an undoubtable original documentation, but at the same time the scarcity of the few saved pages comprises the main research limitation. The elements considered by an “Illiterate” in the accounting field, most significant, as well as the way in which these principles were registered, should be considered in Accounting Education. EL Classifications: D030, D100, M490 Key words: Accounting history, Bookkeeping, Accounting principles, Qualitative analysis